Three Approaches to Using Mixed Reality Simulations for Teacher Preparation and Recruitment of Future Teachers - Shannon Budin (MDPI AG, 2024)
Mixed reality simulations have versatility in both the preparation as well as the recruitment of future teachers. We describe three approaches that have led to successful outcomes for general and special education preservice teachers, as well as in the recruitment of future teacher candidates from the high school level. First, we explored the use of TeachLivE™ to enhance special education teacher candidates' behavior observation skills when conducting functional behavior assessments. Second, we studied the impact of different simulation methods on early childhood candidates' preparedness to communicate with parents and caregivers about sensitive topics. Finally, we utilized TeachLivE™ as a recruitment tool to engage current high-achieving high school students in the teaching and reflection process as part of their on-campus dual credit program. In all cases, candidates and students valued the simulation experiences, recognizing the opportunity to deliver instruction in supportive environments with immediate feedback, coaching, and practice opportunities.